Hubungan Stres Akademik dengan Kualitas Tidur Mahasiswa Keperawatan Tingkat Akhir Program Alih Jenjang - Esthika Ariany Maisa; Andrial Andrial; Dewi Murni; Sidaria Sidaria (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
Sleep is a basic human need. Poor sleep quality can have an impact on students' health and academic performance. Nursing students at the end of the level transfer program have the risk of poor sleep quality due to the high academic task load coupled with other assignments besides lectures that can take up student break time. One of the factors that affect the quality of sleep is stress, and among students it is called academic stress. The purpose of this study was to determine the relationship between academic stress and sleep quality in the final year students of a level transfer program. The study was conducted at one of the campuses in the city of Padang using a correlation analytic research design with a cross sectional approach. The sample in this study amounted to 64 students at the end of the level transfer program with the total sampling technique. This research was conducted from October to November 2019. Data was collected using the Pittsburh Sleep Quality Index and Student Academic Stress Scale research instruments. The results of this study indicate that nursing students at the end of the level transfer program experience poor sleep quality with high academic stress. Correlation analysis provides a linear and positive pattern of relationship between academic stress and sleep quality of nursing students at the end of a level tansfer program, with a very strong correlation strength level, which means that the higher the student's academic stress, the worse the quality of sleep.. It is expected that students can manage academic stress with stress management and time management, so as not to have an impact on the quality of student sleep.